2001
DOI: 10.1063/1.1374499
|View full text |Cite
|
Sign up to set email alerts
|

High-power AlGaInN flip-chip light-emitting diodes

Abstract: Data are presented on high-power AlGaInN flip-chip light-emitting diodes (FCLEDs). The FCLED is “flipped-over” or inverted compared to conventional AlGaInN light-emitting diodes (LEDs), and light is extracted through the transparent sapphire substrate. This avoids light absorption from the semitransparent metal contact in conventional epitaxial-up designs. The power FCLED has a large emitting area (∼0.70 mm2) and an optimized contacting scheme allowing high current (200–1000 mA, J∼30–143 A/cm2) operation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
182
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(190 citation statements)
references
References 6 publications
2
182
0
4
Order By: Relevance
“…[2][3][4][5] One of them consists in using metallic structures to enhance the radiative rate thanks to the surface plasmons they support. 6,7 These plasmon modes have a high local density of states, and consequently catch the main part of the emission, which can then be coupled to radiative light with a corrugation (either periodic 6 or not 8,9 ).…”
mentioning
confidence: 99%
“…[2][3][4][5] One of them consists in using metallic structures to enhance the radiative rate thanks to the surface plasmons they support. 6,7 These plasmon modes have a high local density of states, and consequently catch the main part of the emission, which can then be coupled to radiative light with a corrugation (either periodic 6 or not 8,9 ).…”
mentioning
confidence: 99%
“…Figure 3 shows the substantial progress that has been made in the past few years in increasing the luminous flux obtained from single LEDs driven at high current densities. 12 Typical conventional LED indicator lamps are 0.25 mm square and are mounted in packages that can handle about 0.1-W input power. High-performance chips have an output of 1-2 lumens per device.…”
mentioning
confidence: 99%
“…18 They concluded that the silver-loaded epoxy outperforms benzocyclobutene for doubling the achievable current while it keeps the EQE above 50%. With a very similar flip-chip and metal bonding processes in nitride material systems, 21 Haerle et. al.…”
Section: Extraction Approachesmentioning
confidence: 99%